RANCANGAN BUKU KERJA PENGUATAN PENGETAHUAN TEKNOLOGI BAGI GURU IPA SMP - Dewita, Dea; Suryawati, Evi; ', Arnentis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Technological Pedagogical and Content Knowledge (TPACK) is a conceptual framework that shows the relationship between three kinds of knowledge needed by the teacher or prospective teacher including technological knowledge, pedagogical knowledge, and content knowledge. The objective of this study was to develop a workbook of Technological Knowledge (TK) for Stregthening Natural Science Teacher Competencies. The book was developed from essential indicator of Teacher Competency Test. Design, develop, simulation and validation of workbook by internal validator conducted at the Laboratory of Biology Education FKIP University of Riau. External validation by experts, pilot test and user response of the workbook in MGMP IPA Pekanbaru. Workbooks validated on four aspects of the Technological Knowledge include format, content, illustrations and language. Validated workbook will be disseminate after revised. The workbook can be used as a learning resource by the teachers to improve technology competencies and teaching and learning process.Keywords: Natural Science Teacher, Technological Knowledge, Workbook